# How do you solve using elimination of #4x+3y= -1# and #2x+5y=3#?

##### 1 Answer

Nov 9, 2015

#### Answer:

The final answer would be :

#### Explanation:

- In elimination, you need to get two variables in the equations to cancel out. The easiest ones would be 2x and 4x. Also, you get variables to cancel out when they are both the same number except one is negative.
- In order to turn 2x into -4x, we would multiply that equation by -2, turning the equation into:
#-4x-10y=-6# . - The x variables would cancel out each other, and you would add the other two variables. 3y + -10y = -7y, and -6 + -1 = -7. This results in
#-7y=-7# .

You divide -7 on both sides resulting in#y=1# . - You go back to your original equations and plugging in 1 for y, which results in
#4x+3=-1# and#2x+5=3# . - For
#4x+3=-1# , you would subtract 3 on both sides and divide by 4 on both sides, resulting in#x=-1# . You then subtract 5 from#2x+5=3# on both sides and than dividing by two, which results in#x=-1# . - Your final answer is
#y=1# and#x=-1# .